1999
DOI: 10.1159/000025622
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Biology of the Vascular Smooth Muscle Cell: Building a Multilayered Vessel Wall

Abstract: The assembly of the vessel wall from its cellular and extracellular matrix components is a critical process in the development and maturation of the cardiovascular system. However, fundamental questions concerning the origin of vessel wall cells and the mechanisms that regulate their development and differentiation remain unanswered. The initial step of vessel wall morphogenesis is formation of a primary vascular network, comprised of nascent endothelial cell tubes, via the processes of vasculogenesis and angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
183
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(201 citation statements)
references
References 228 publications
10
183
0
5
Order By: Relevance
“…In fact, all the quail-to-chick proepicardial chimeric transplantation studies show a gradient in the expression of SMC markers from the media to the non-SMC adventitia of the coronaries. The close ontogenetic relationship between SMCs and fibroblasts has been discussed previously (Hungerford and Little, 1999). Finally, it has been demonstrated that non-epicardiallyderived fibroblasts can transdifferentiate and give rise to other cells types (Kon and Fujiwara, 1994).…”
Section: Epdcs and Cardiac Fibroblastsmentioning
confidence: 67%
“…In fact, all the quail-to-chick proepicardial chimeric transplantation studies show a gradient in the expression of SMC markers from the media to the non-SMC adventitia of the coronaries. The close ontogenetic relationship between SMCs and fibroblasts has been discussed previously (Hungerford and Little, 1999). Finally, it has been demonstrated that non-epicardiallyderived fibroblasts can transdifferentiate and give rise to other cells types (Kon and Fujiwara, 1994).…”
Section: Epdcs and Cardiac Fibroblastsmentioning
confidence: 67%
“…The transition from a differentiated phenotype to a fibroblast-like proliferative state is observed during the onset or progression of atherosclerosis (2-3), one of the most common diseases in developed countries (4 -5). Under these conditions, the VSM cell phenotype is reminiscent of that observed during vascular development, where VSM cells play a key role in morphogenesis of the blood vessel and exhibit a high proliferative index, migrate, and produce extracellular matrix components (6). Conditions that promote the proliferative phenotype include the combined action of growth factors, proteolytic enzymes, and exposure to extracellular matrix proteins (7).…”
mentioning
confidence: 99%
“…VSMC begin differentiation as "fibroblast-like" cells, lacking myofilaments and basement membranes and appearing as aggregates near embryonic EC. 25 Cell lineage studies in birds suggest that aortic arch VSMC are derived from ectoderm (ie, neural crest), whereas VSMC in other sites are mesodermally derived. However, there is also evidence that embryonic avian dorsal aortic EC transdifferentiate into myofilament-expressing mesenchymal cells.…”
mentioning
confidence: 99%